Create, copy, disrupt : India's intellectual property dilemmas - Reddy, Prashant; Chandrashekaran, Sumathi (New Delhi : Oxford University Press, 2017)
This title unravels the development of India's intellectual property law and policy in modern times, through chapters focusing on different industries and sectors such as such as pharmaceuticals, publishing, cinema, music, and the Internet.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 22, 2017).
Keywords: Intellectual property -- India; Law; Laws of specific jurisdictions & specific areas of law